2017
DOI: 10.1002/ps.4757
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cycloxaprid in Laodelphax striatellus is associated with altered expression of nicotinic acetylcholine receptor subunits

Abstract: The findings indicate that resistance to cycloxaprid develops slowly compared with resistance to other chemicals and without cross-resistance to chlorpyrifos or buprofezin; over-expressed Lsα1 is associated with low cycloxaprid resistance levels, but the importance of over-expressed Lsβ1 and reduced expression of Lsα8 could not be excluded. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Cycloxaprid exhibited high bioactivity against a series of insect pests, such as N. lugens, Apolygus lucorum, Laodelphax striatellus, and Bemisia tabaci, especially for the imidacloprid-resistant populations of A. gossypii and N.…”
Section: Introductionmentioning
confidence: 99%
“…Cycloxaprid exhibited high bioactivity against a series of insect pests, such as N. lugens, Apolygus lucorum, Laodelphax striatellus, and Bemisia tabaci, especially for the imidacloprid-resistant populations of A. gossypii and N.…”
Section: Introductionmentioning
confidence: 99%
“…The transcripts of nAChR β1 and α1 subunits were unregulated in the selected resistant strain of L. striatellus . In our transcriptomic data, the low-level transcription of six α subunits and a β1 subunit was detected.…”
Section: Resultsmentioning
confidence: 60%
“…The molecular target of CYC is the nAChRs, which are upregulated in a resistant strain of L. striatellus . However, in this study, no nAChRs were identified as DEGs (Table S1).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Studies have demonstrated that not only decreased expression but also increased expression of nAChR subunit genes were associated with the development of resistance to neonicotinoids of insects. The expression of Lsα1 and Lsβ1 was significantly increased in cycloxaprid‐resistant and IMI‐resistant populations of L. striatellus , respectively, while Lsα8 was significantly downregulated (Zhang et al ., 2018a, 2018b). Conversely, Boα8 was found to be significantly upregulated in highly IMI‐resistant populations of B. odoriphaga , whereas Boα1 and Boβ1 were significantly downregulated (Shan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%